If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = 4yx + -1x Reorder the terms: 3y = -1x + 4xy Solving 3y = -1x + 4xy Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4xy' to each side of the equation. -4xy + 3y = -1x + 4xy + -4xy Combine like terms: 4xy + -4xy = 0 -4xy + 3y = -1x + 0 -4xy + 3y = -1x Reorder the terms: x + -4xy + 3y = -1x + x Combine like terms: -1x + x = 0 x + -4xy + 3y = 0 The solution to this equation could not be determined.
| 3(x+1)+2(x+4)= | | x+3.5x+20=56 | | 9x-6x=8 | | 3(4y+2)+7y= | | 8x^2-2x+2=0 | | 6(u-9)-1=-5(-3u+8)-3u | | 5+(9+18-3)-3= | | 7(m+5)=22 | | 8-n=34 | | 7nsquared+7=12n | | 2(4x+3)+6= | | -56=88-9x | | 29-7x=28x-28 | | 9+14x+5x=180 | | 7-2f=1.98 | | 10-2y+4x=0 | | -7[4+7(-5+7)]+16= | | 50+3b=134 | | 3(1)=3 | | 7x+6=2z+2 | | 12x-13=-6x | | 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 | | 3l+4-4l=-3 | | 53+18w=c | | 7x-4=37 | | 3(t-3)-2t=-30 | | (2m+3t)(3m-4t)= | | y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 |